The Effectiveness of Video-Assisted Flipped Classroom Learning Model Implementation in Integral Calculus - Afaniah Fahreny Jafar; Rusli Rusli; Muhammad Dinar; Irwan Irwan; Hastuty Hastuty (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aimed to determine the effectiveness of applying video-assisted flipped classroom learning models in integral calculus courses. The effectiveness of learning in this study was measured based on the achievement of learning outcomes, student activities during learning, and student responses. This study was a pre-experimental study with a purposive sampling technique. The data collection method used two tests, observation sheets, and two questionnaires. Data analysis techniques were conducted by using statistical and inferential descriptive analysis. The results of the analysis showed: (1) The score of student learning outcomes has increased reaching a minimum completeness score of 70 with an average score of student learning outcomes in posttest 1 and posttest 2 of 75.28 and 78.09, (2) The average student activity is in the very active category, and (3) The average percentage of student response questionnaires on two response questionnaires, namely student response to the implementation of mathematics learning is amounted to 88%, and student response to instructional video media is amounted to84%. In general, it can be concluded that the video-assisted flipped classroom learning model is effective to be applied in mathematics learning.